Environment and people : an intergrated course for A and AS geography - Environment and people; Witherick, Michael ([S.l.] : Nelson Thornes, 1995)
Written to meet the requirements of the revised A-Level/AA-Level syllabuses effective from June 1997 examinations, this book provides materials which offer an integrated approach to geography. Eight themes are followed and flagged throughout - systems, hazards, pollution, sustainability, health and well-being, leisure and recreation, competition and conflict, and environmental change. In addition, two integrating places of contrasting scale, environment and development level are defined and appear recurrently throughout the units - Tokyo and Japan, and India and neighbouring states.
Keywords: enviroment,people,geography